2014
DOI: 10.1371/journal.pone.0104103
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Proteomics Differentiates Cholesteatoma from Surrounding Tissues and Identifies Novel Proteins Related to the Pathogenesis

Abstract: Cholesteatoma is the growth of keratinizing squamous epithelium in the middle ear. It is associated with severe complications and has a poorly understood etiopathogenesis. Here, we present the results from extensive bioinformatics analyses of the first large-scale proteomic investigation of cholesteatoma. The purpose of this study was to take an unbiased approach to identifying alterations in protein expression and in biological processes, in order to explain the characteristic phenotype of this skin-derived t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Finally, competition by synthetic peptides that contain the targeted phage-displayed peptide sequence to compete with phage for binding implicates a receptor-mediated process for binding and translocation. While epithelia form protective barriers throughout the body, trans-epithelial transport of molecules and cells is common 54 , and is often required for normal epithelial function. For example, transport of antibodies and surveillance immune cells is part of the normal biology of all mucosae (e.g., gut and ME).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, competition by synthetic peptides that contain the targeted phage-displayed peptide sequence to compete with phage for binding implicates a receptor-mediated process for binding and translocation. While epithelia form protective barriers throughout the body, trans-epithelial transport of molecules and cells is common 54 , and is often required for normal epithelial function. For example, transport of antibodies and surveillance immune cells is part of the normal biology of all mucosae (e.g., gut and ME).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes are also able to transit epithelial barriers via paracellular transport 56 , separating intercellular junctions in the process, to cross into mucosal lumens such as in the ME cavity during OM 57 . An alternative mechanism is trans-cellular transport, using cell surface receptors, which can occur in either a basolateral or laterobasal direction 54 . While molecules can move into and through a cell by passive diffusion, they are moved far more efficiently by active transport, including carrier- and receptor- mediated systems.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that expression profile of cholesteatoma is similar to a metastatic tumor [4]. Britze, et al [5] demonstrated that several differentially expressed proteins related with cancer may cause cancer-like alterations and reorganization of the tissue. Taken together, these observations support that cholesteatoma has genetic instability.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, several differentially expressed proteins related with cancer were shown in cholesteatoma comparing to corresponding skin lesions. It was reported that these proteins might cause cancer-like alterations and reorganization of the tissue that may explain the characteristic phenotype of the disease [5]. There are not any medical therapies for cholesteatoma and the only applied treatment now is surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of several extracellular matrices and basement membrane proteins (such as COL18A1 and NID2) observed may have a major impact on tissue integrity. The up-regulation of ELANE and pro-inflammatory S100 proteins (eg S100A7A and S100A7) is mainly regulated biological areas in cholesteatoma (16).…”
Section: Introductionmentioning
confidence: 99%